Molecular characterization of kappa class glutathione S-transferase from the disk abalone (Haliotis discus discus) and changes in expression following immune and stress challenges. Issue 77 (June 2018) - Sandamalika, W.M. Gayashani; Priyathilaka, Thanthrige Thiunuwan; Liyanage, D.S.; Lee, Sukkyoung; Lim, Han-Kyu; Lee, Jehee
Abstract: Glutathione S-transferase (GST; EC 2.5.1.18) isoenzymes represent a complex group of proteins that are involved in phase II detoxification in several organisms. In this study, GST kappa (GSTκ) from the disk abalone ( Haliotis discus discus; AbGSTκ ) was characterized at both the transcriptional and functional levels to determine its potential capacity to perform as a detoxification agent under conditions of different stress. The predicted AbGSTκ protein consists of 227 amino acids, with a predicted molecular weight of 25.6 kDa and a theoretical isoelectric point (pI) of 7.78. In silico analysis reveals that AbGSTκ is a disulfide bond formation protein A (DsbA), consisting of a thioredoxin domain, GSH binding sites (G-sites), and a catalytic residue. In contrast, no hydrophobic ligand binding site (H-site), or signal peptides, were detected. AbGSTκ showed the highest sequence identity with the orthologue from pufferfish ( Takifugu obscurus ) (60.0%). In a phylogenetic tree, AbGSTκ clustered closely together with other fish GSTκs, and was evolutionarily distanced from other cytosolic GSTs. The predicted three-dimensional structure clearly demonstrates that the dimer adopts a butterfly-like shape. A tissue distribution analysis revealed that GSTκ was highly expressed in the digestive tract, suggesting it has detoxification ability. Depending on the tissue and time, AbGSTκ showed different expression patterns, and levels of expression, following challenge of the abalone with immune stimulants. Enzyme kinetics of the purified recombinant proteins demonstrated its conjugating ability using 1-Chloro-2, 4-dinitrobenzene (CDNB) and glutathione (GSH) as substrates, and suggested it has a low affinity for both substrates. The optimum temperature and pH for the rAbGSTκ GSH: CDNB conjugating activity were found to be 35 °C and pH 8, respectively indicating that the abalone is well adapted to a wide range of environmental conditions. Cibacron blue (100 μM) was capable of completely inhibiting rAbGSTκ (100%) with an IC50 (half maximal inhibitory concentration) of 0.05 μM. A disk diffusion assay revealed that rAbGSTκ could significantly protect cells from H2 O2, CdCl2, and ZnCl2 . Altogether, this current study suggests that AbGSTκ is involved in detoxification and immunological host defense mechanisms and allows abalones to overcome stresses in order for them to have an increased chance of survival. Highlights: The full-length coding sequence of AbGSTκ was identified in disk abalone. AbGSTκ is a disulfide bond formation protein A (DsbA) with a thioredoxin domain. Highest mRNA expression of AbGSTκ was observed in digestive tract. Immunological responses of AbGSTκ has evaluated. Enzyme kinetics, optimum conditions and heavy metal stress responses were measured.